Analisis Kebutuhan Media Digital Interaktif dalam Pembelajaran STEAM untuk Memfasilitasi Perkembangan Kognitif Anak Usia Dini - Anissa Salsabila, Siti Rahma; Rahman, Taopik; Qonita, Qonita (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This research is motivated by the suboptimal use of digital media in schools for learning. The purpose of this study is to analyze the need for developing interactive digital media in STEAM learning. This study uses the Educational Design Research (EDR) method with a qualitative approach, through observations and interviews with four early childhood education institutions in Tasikmalaya City. The results show that schools have not optimally utilized the digital media provided by the school. Media use in learning is 70% for YouTube videos, 15% for PPT, and 10% for quiz-based games. This is due to teachers' lack of understanding of digital media usage, so they cannot utilize it optimally. The results show that 90% of children are more focused and understand the material delivered through digital media. Therefore, digital media affects cognitive abilities, especially in the ability to understand concepts and materials. Based on the findings, it shows the potential to develop interactive digital media in STEAM learning for early childhood to facilitate cognitive developmen